HIV/AIDS awareness and attitudes of mineworkers: A case study - C. DeW. Van Wyk; N. D. Tshivase (South African Journal of Business Management, 2005)
The central question to be examined revolves around the attitudes and awareness of HIV/AIDS among mineworkers at a mine. Semi-standardised questionnaires were used to conduct in-depth interviews on a one-on-one basis. The findings revealed that workers had a great lack of knowledge about AIDS. While some workers had a detailed knowledge of the disease and its prevention, others were either completely ignorant about it or were in denial of its existence. The study serves as a tool and a framework of reference to the mine management on the areas of concern, to put great emphasis on IEC, in order to combat the spread of the disease in the mine. Recommendations are proposed for future research, policy making and practice in the area of HIV/AIDS.These will be in line with the factors influencing mineworkers' perceptions of the epidemic.
Keywords: 650